LE MYTHE DU VAMPIRE FÉMININ DANS "MADEMOISELLE CHRISTINA" - Léna HOBEIKA (Studia Universitatis Babeş-Bolyai. Philologia, 2021)
The Myth of the Female Vampire in Miss Christina. Mythologist, novelist and religious historian, Mircea Eliade grants a considerable place to the Fantastic as a way of reclaiming the Sacred in a deeply desecrated modern world. In his short story Mademoiselle Christina, he features a female vampire embodying the archetype of the nymphomaniac and demonic woman who returns to haunt the Mosco house and who manages to seduce Egor, a young painter visiting the castle. The prose writer creates a dreamlike story, mixing dream and reality, the natural and the supernatural while propelling the reader into a strange and captivating scenario. In this sense, it would be interesting to first study the poetics of the fantastic tale as well as its different mechanisms which contribute to creating a feeling of disturbing strangeness, "the unheimlich". Then we will analyze the erotic dynamics of the female vampire as well as its various symbolisms in order to finally offer a hermeneutical and mythical-symbolic approach to the work, where the reader will be led to decrypt the symbols and signs of the Sacred, camouflaged in reality.